Utilization of fodder banks - Bayer, W. (International Livestock Centre for Africa, 1984)
Presents 3-year results testing weight losses of cattle on 2 or 4-hour dry season grazing of fodder banks, compared to controls, within ILCA's subhumid zone programme in Nigeria and observations on diet selection and grazing activity on fodder banks and natural range.